ITherm 2002. Eighth Intersociety Conference on Thermal and Thermomechanical Phenomena in Electronic Systems (Cat. No.02CH37258)
DOI: 10.1109/itherm.2002.1012556
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of microvia reliability

Abstract: Dramatic advances in electronic industry have lead to higher VO, finer pitch and smaller footprint off chip interconnects to meet the cost, performance and size requirements. Microvia substrate technologies will play a crucial role in the printed wiring board (PWB) industry to accommodate these high VO chips. A comprehensive experimental and theoretical program is underway at the Georgia Institute of Technology to develop the microvia substrate technologies. The experimental aspect of this program involves fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Control of the copper plating process is a key factor for improving yield and reliability of microvias. [7] Solder is then deposited in the microvia filling the hole.…”
Section: Microvia Manufacturingmentioning
confidence: 99%
“…Control of the copper plating process is a key factor for improving yield and reliability of microvias. [7] Solder is then deposited in the microvia filling the hole.…”
Section: Microvia Manufacturingmentioning
confidence: 99%
“…7(a)] and material interaction effects [ Fig. 7(b)] in developing predictive models and up-front design guidelines for SOP system board fabrication [18], [19].…”
Section: ) Digital Function Reliability: Upfront Process Optimizatiomentioning
confidence: 99%
“…Microvia reliability research has primarily centered around the core focuses of design optimization and understanding the failure mechanisms of microvias. Some researchers have focused on experimental investigations of the reliability of single level microvias [19], [20]. Some publications have addressed the microvia reliability of single level unfilled or epoxy-filled microvias.…”
Section: Introductionmentioning
confidence: 99%
“…Birch [25] tested stacked electroplated microvias and found that two-level stacked microvias are relatively more reliable than four-level stacked microvias. Previous research has found different types of failure in microvias including cracks around corners, knees, pads, and interfacial separation [19], [20], [21]. Ning et al [26] investigated the voiding effect on the reliability of copper-filled stacked microvias in detail with different characteristics of voiding such as void shapes, location, and sizes.…”
Section: Introductionmentioning
confidence: 99%